Analisa Simulasi Kekuatan Rangka pada Mesin Brush Sander menggunakan Aplikasi Solidwork - Fardana, Fendi; Rhohman, Fatkur (Universitas Sriwijaya, 2024)
This research aims to analyze the strength and response of the brush sunder machine frame to forces and loads. The research method utilizes the SolidWorks application with a frame made of angle iron and ASTM 36 material. The research results encompass critical data such as stress, displacement, and safety factors. The application of forces and loads on the frame through the SolidWorks model enables a thorough evaluation of the structural strength and its response. Stress data provides an overview of maximum loads, displacement identifies deformations, and safety factors indicate the level of structural reliability. The results show values of deformation at 1.09 mm, stress at 4.8 N/m, Strain at 4.2, and FOS at 1.87. These values are within safe limits. This research is expected to contribute to a better understanding of the performance and safety of the brush sunder machine frame under various operational conditions.